Trading the bond-CDS basis: The role of credit risk and liquidity - Monika Trapp (University of Cologne, Centre for Financial Research (CFR), 2009)
We analyze trading opportunities that arise from differences between the bond and the CDS market. By simultaneously entering a position in a CDS contract and the underlying bond, traders can build a default-risk free position that allows them to repeatedly earn the difference between the bond asset swap spread and the CDS, known as the basis. We show that the basis size is closely related to measures of company-specific credit risk and liquidity, and to market conditions. In analyzing the aggregate profits of these basis trading strategies, we document that dissolving a position leads to significant profit variations, but that attractive risk-return characteristics still apply. The aggregate profits depend on the credit risk, liquidity, and market measures even more strongly than the basis itself, and we show which conditions make long and short basis trades more profitable. Finally, we document the impact of the financial crisis on the profits of long and short basis trades, and show that the formerly more profitable long basis trades experienced stronger profit decreases than short basis trades.
Keywords: C31; C32; G12; G13; G14; G32; 330; bond asset swap spreads; CDS premia; basis trading profits; credit risk; liquidity; fixed-effects; vector error correction model; Anleihe; Credit Default Swap; Wertpapierhandel; Rentabilität; Kreditrisiko; Marktliquidität; Fehlerkorrekturmodell; Schätzung; Schätzung; Deutschland